Pemanfaatan Teknologi dalam Meningkatkan UMKM Krupuk Stik “Barokah Jaya” Desa Kedungbanteng - Yunita Ramadhani; Nafiah Nafiah; Khoirul Fathoni (Social Science Academic, 2025)
Barokah Jaya Krupuk Stik MSMEs are one of the small and medium businesses that focus on the production and marketing of stick crackers. Despite having quality products, challenges in marketing and distribution often hinder the growth of this business. This study aims to determine the use of technology in improving "Barokah Jaya" Krupuk Stik MSMEs in Kedungbanteng Village, Sukorejo District, Ponorogo Regency. In addition, this study aims to examine the use of technology in improving the performance of "Barokah Jaya" Krupuk Stik MSMEs, especially in the aspects of marketing, production, and operational management. The method used in this study is ABCD (Asset Bassed Community Driven-Development) which empowers the use of technology to improve the marketing of an MSME. The result of this research is to improve the quality of "Barokah Jaya" Krupuk Stik MSMEs, especially in terms of marketing through Instagram social media accounts managed by Mr. Hendro as the owner of "Barokah Jaya" Krupuk Stik MSMEs. In addition, the results of this study show that the adoption of technology not only increases the competitiveness of Krupuk Stik Barokah Jaya in the local market, but also opens up opportunities for expansion into the national market.